Association between prevalence of human leptospirosis infection and gender in Hospital Melaka / Farah Aminah Hamka - Hamka, Farah Aminah (2014)
Leptospirosis is one of the common re-emerging zoonotic diseases transmitted from infected animals to human. It is a bacterial infection caused by a species of pathogenic leptospiragenus called spirocheates. Pathogenic leptospires live in the kidneys of many mammalian hosts, including rodents, insectivores, and livestock. Leptospires are shed into the environment, where they can survive for several months in favorable condition. The first case of human leptospirosis in Malaysia was discovered by Fletcher in the year 1925. The aim of the present study was to determine the association between prevalance and gender of patient infected with Leptospirosis in Hospital Melaka. The medical records of hospital department in Hospital Melaka were used to identify records of patients infected with leptospirosis from January 2013 until May 2014. The laboratory testing for leptospiral infection is important both for diagnosis and management of patients. In this study, the result was obtained from Rapid IgM Elisa test method. The patient data was collected for positive leptospirosis cases reported in Hospital Melaka, where 791 cases detected over the study period. 65% were male patient and 35% were female patient. The risk of leptospiral infections with respect to gender were demonstrated in this study. It is highlighted that the majority of leptospirosis cases were men due to association of man with animal and disease-infected environment. This result revealed that male have the highest prevalence of leptospiral infection compare to female.